2019
DOI: 10.1002/jms.4448
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen‐induced protein aggregation: Lysozyme crosslink formation and nLC‐MS/MS characterization

Abstract: Singlet molecular oxygen ( 1 O 2 ) has been associated with a number of physiological processes. Despite the recognized importance of 1 O 2 -mediated protein modifications, little is known about the role of this oxidant in crosslink formation and protein aggregation. Thus, using lysozyme as a model, the present study sought to investigate the involvement of 1 O 2 in crosslink formation. Lysozyme was photochemically oxidized in the presence of rose bengal or chemically oxidized using [ 18 O]-labeled 1 O 2 relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Oxidative dimerization (and oligomerization) of peptides through cross-linking between oxidized His and nucleophilic amino acid residues such as Lys or His was previously reported (Fig. 5C) (30)(31)(32)(33). Accordingly, catalyst 7 photooxygenated A present in low concentrations in brain lysate containing a large number of off-target molecules.…”
Section: Photooxygenation Of A In the Mouse Brainmentioning
confidence: 66%
“…Oxidative dimerization (and oligomerization) of peptides through cross-linking between oxidized His and nucleophilic amino acid residues such as Lys or His was previously reported (Fig. 5C) (30)(31)(32)(33). Accordingly, catalyst 7 photooxygenated A present in low concentrations in brain lysate containing a large number of off-target molecules.…”
Section: Photooxygenation Of A In the Mouse Brainmentioning
confidence: 66%
“…Recently, E. F. Marques et al proved, using mass spectrometry, that 2′ oxo-histidine can react with Trp, Lys or other His residues, leading to cross-link formation and aggregation in lysozyme. Additionally, it was shown that oxidized forms of tryptophan could cross-link to histidine or to other tryptophan moieties [ 46 ]. Additionally, S. Jiang et al described a novel disulphide CL pathway, based on the photo-oxidation of disulphide bonds, which leads to reactive intermediates that on their turn give rise to new protein–protein cross-links ( vide infra Section 3.1.2 ) [ 47 ].…”
Section: Reaction Of Singlet Oxygen With Biomoleculesmentioning
confidence: 99%
“…It was proven that 1 O 2 was involved in the generation of cross-links between oxidized histidine, histidine, lysine and kynurenine derivative of trypthophan. Additionally, cross-links between oxidized trypthophan and the open ring kynurenine derivative were seen [ 46 ]. A small overview on the types of protein cross-links and high molecular mass aggregates is given by E. Fuentes-Lemus et al, combined with the relation of photo-oxidation of protein with pathological conditions [ 137 ].…”
Section: 1 O 2 In Bioorganic Chemistry Ap...mentioning
confidence: 99%
See 1 more Smart Citation
“…Di Mascio and co-workers have studied the generation of singlet oxygen ( 1 O 2 ) in biological systems-see, for example, [4]-showing the generation of 1 O 2 from lipid hydroperoxides and nitronium ions. This group has also shown that 1 O 2 is involved in the formation of covalent crosslinks involving histidine, lysine, and tryptophan [5].…”
Section: Introductionmentioning
confidence: 99%